Nerves, Vibration and the Aeolian Harp - Trower, Shelley (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2009)
AbstractThis essay examines how the Aeolian harp functions as a model for the workings of the human nervous system as understood in the late eighteenth and early nineteenth centuries. It sets out the scientific contexts – ranging from Hartleyan associationism to medical theories regarding the origin of life – that informed, in particular, two of Coleridge’s best-known poems: “The Aeolian Harp” and “Dejection: An Ode.” The essay provides a materialist account of mind, emphasising its inseparability from the body and physical world, as a corrective to the tendency in past criticism to overemphasize the transcendental aspect of the Romantic worldview and its attendant poetics. Further, it develops the insights of critics such as Jonathan Crary who have previously focused on optical instruments and vision by turning instead to a sonorous model for the self.